Smart healthcare in the IoT era: a context-aware recommendation example - Casino, F.; Patsakis, C.; Batista, E.; Postolache, O.; Martínez-Ballesté, A.; Solanas, A. (2018 International Symposium in Sensing and Instrumentation in IoT Era, ISSI 2018, 2018)
Smart cities are progressively gaining importance due to the worldwide process of urbanisation that is taking place and the need for more sustainable and liveable cities. In the context of a smart city, networks of interconnected heterogeneous devices provide lots of data. In addition, citizens have the possibility of using their smartphones to share information with the city and with other users, thus contributing to the overall infrastructure. With the aim to use the infrastructure of modern smart cities to improve the quality of life of citizens and their healthcare system, the concept of smart health (s-health) was born. In this article, we show how recommendation systems could be used to provide healthcare services within the context of a smart city in which citizens collaborate with the city to improve their quality of life. We describe the architecture and implementation details of a smart health application and set the foundations for further research lines that are briefly pointed out.